2000
DOI: 10.1086/313397
|View full text |Cite
|
Sign up to set email alerts
|

Jet Directions in Seyfert Galaxies: B and I Imaging Data

Abstract: We present the results of broadband B and I imaging observations for a sample of 88 Seyfert galaxies (29 Seyfert 1s and 59 Seyfert 2s), selected from a mostly isotropic property, the Ñux at 60 km. We also present the B and I imaging results for an additional sample of 20 Seyfert galaxies (7 Seyfert 1s and 13 Seyfert 2s), selected from the literature and known to have extended radio emission. The I-band images are Ðtted with ellipses to determine the position angle and ellipticity of the host galaxy major axis.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 12 publications
(12 reference statements)
8
27
0
Order By: Relevance
“…Thus we discard the values from the second catalog. The mean of our values are also in general agreement with the photometric values, except for the case of the I photometry by Schmitt & Kinney (2000) who give a higher PA value than the rest. We adopt the mean values of the results of our two methods applied to the first and third catalog.…”
Section: Notes On Individual Galaxiessupporting
confidence: 88%
See 1 more Smart Citation
“…Thus we discard the values from the second catalog. The mean of our values are also in general agreement with the photometric values, except for the case of the I photometry by Schmitt & Kinney (2000) who give a higher PA value than the rest. We adopt the mean values of the results of our two methods applied to the first and third catalog.…”
Section: Notes On Individual Galaxiessupporting
confidence: 88%
“…Our two methods do not work properly because they try to circularize the ring. We adopt the deprojection angles obtained in the photometric study of Schmitt & Kinney (2000).…”
Section: Notes On Individual Galaxiesmentioning
confidence: 99%
“…MCG−1−24−12 has an optical magnitude of m v = 15 and it is in the 2MASS catalogue (m J = 14.2, m H = 13.3, m K = 12.8); it belongs to the 60 µm sample of warm IRAS galaxies (de Grijp et al 1992;Kinney et al 2000) with a log (L FIR ) = 10.01 L (Chatzichristou 2000). It is also a radio galaxy with a F 3.6 cm = 9.1 mJy and its 3.6 cm radio contours show a ∼70 pc elongation towards the west (Schmitt et al 2001), but it was never observed in the X-ray band. After finding MCG−1−24−12 as the possible candidate, we were able to obtain a pointed observation with BeppoSAX and found that its 2-10 keV flux of ∼1 × 10 −11 erg cm −2 s −1 is more consistent with that reported in the original Piccinotti source list (Piccinotti et al 1982) than that observed from EXO0917.3−0722.…”
Section: Observations: From Exo09173−0722 To Mcg−1−24−12mentioning
confidence: 93%
“…In addition to the RGS spectra we also investigate the nature of the host galaxy using archive B-band and I-band images, from 1.2 ks exposures in November 1998 with the 1 m Nickel Telescope at the Lick Observatory (Schmitt & Kinney 2000), and combined UV images, from the XMM-Newton Optical Monitor (XMM-OM, Mason et al 2001) taken simultaneously with the RGS observations mentioned above. The pipeline processed XMM-OM UV sky-images in each filter were aligned and then coadded to produce the image of Arakelian 564 for each of the UVW1 (220−400 nm), UWM2 (200−280 nm) and UVW2 (180−260 nm) filters.…”
Section: Observations and Data Reductionmentioning
confidence: 99%